Efforts to Build a Pancasila Economy: Making Nusantara Local Wisdom the Antithesis of Neo-Capitalism - Suhardi Somomoeljono (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2026)
This study explores the conceptual and structural efforts to build a New Paradigm of the Pancasila Economic System, positioning it as a direct, humane alternative to the destructive tendencies of Neo-Capitalism. Grounded in the constitutional mandate of the Fifth Sila (Social Justice for All Indonesian People), this paper argues that the modern formulation of Pancasila Economics must derive its core postulates from the rich soil of Nusantara's local wisdom. Using a qualitative-descriptive approach and conceptual-philosophical analysis, this research deconstructs the hyper-individualism and market tyranny of Neo-Capitalism, contrasting them with time-tested indigenous practices such as Gotong Royong (mutual cooperation), Musyawarah (deliberation), and localized ecological management frameworks like Subak and Sasi. The findings demonstrate that by structuring these communal values into a formal macroeconomic model, capital can be subjected to ethical, social, and spiritual boundaries, ensuring equitable wealth distribution over corporate greed. Furthermore, this study addresses the harsh reality of systemic domestic corruption, asserting that true nation-building demands unwavering academic resilience. Ultimately, this paper offers a rigorous conceptual framework that serves as an act of intellectual decolonization, proving that Indonesia's economic sovereignty lies in reclaiming its ancestral, egalitarian roots.